ANTIBODIES TO LEUKEMIA DIFFERENTIATION FACTOR (HLDF) IN PATIENTS WITH GASTROINTESTINAL CANCER - A. I. Autenshlus; A. V. Sosnina; E. S. Mikhailiva; A. P. Lykov; Yu. V. Tumanov; E. D. Danilanko; V. S. Samukov; I. A. Kostanyan; D. V. Morozov; M. M. Cherenkova; L. .A. Thvan; N. A. Varaksin (Медицинская иммунология, 2014)
Antibodies to leukemia differentiation factor (HLDF) in patients with gastrointestinal cancer Abstract. Patients with gastric cancer exhibit higher levels of IgG4-antibodies to human leukemia differentiation factor (HLDF), as compared with healthy individuals, whereas, in patients with colorectal cancer, one may detect high levels of IgA anti-HDLF antibodies, along with lower levels of IgG1 class antibodies against HLDF than in control group. Among patients with gastrointestinal cancer, a positive correlation is revealed between contents of highly differentiated cells in the tumor, and IgM antibodies to HDLF. Meanwhile, a reverse relationship is noted between low differentiation of tumor cells and levels of IgG2 antibodies to HDLF in gastric cancer patients, or IgG3 antibodies to HDLF in patients with colorectal cancer.